Ecophysiology of annual legumes - Pozo A. del; Aronson J. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
We review and briefly analyse some of the main ecophysiological attributes found in annual legumes in evolutionary and ecological response to the environmental factors affecting their development, reproduction and survival in Mediterranean Type Ecosystems. We also give some examples of inter-and intra-specific differences that need to be taken into account when introducing or disseminating annual legumes for pasture improvement, rehabilitation efforts, erosion control and-or long term soil restoration programmes.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)